SEM Analysis in the Effect of Service Quality on Customer Satisfaction and Its Implications on Student’s Loyalty Online Transportation Users in Madiun Municipality - Tatik Mulyati; Saraswati Budi Utami (Journal of International Conference Proceedings (JICP), 2019)
Online transportation is trend of modern transportation models in various countries in the world, including Indonesia. This transportation is very attractive to the public because it can reduce the consumption of the number private vehicles, lower cost and more efficient. This study aims to determine the effect of service quality on customer loyalty with customer satisfaction as moderating variable. Data collection instruments using questionnaire, with purposive sampling approach. The population was students of 6 colleges in Madiun City. The analysis technique uses validity and reliability test, multiple linear regression, classic assumption test, hypothesis test and moderation test.The results showed that service quality and customer satisfaction contributed to consumer loyalty. T test results concluded that the quality of service affects customer loyalty. Consumer satisfaction affects customer loyalty. Simultaneously the quality of service has significant effect on customer loyalty with customer satisfaction as moderating variable.